2016
DOI: 10.1038/srep29253
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular transfer of P-glycoprotein in human blood-brain barrier endothelial cells is increased by histone deacetylase inhibitors

Abstract: The blood–brain barrier (BBB) controls the entry of compounds into the brain, thereby regulating brain homeostasis. Efflux transporters such as P-glycoprotein (Pgp) significantly contribute to BBB function. Multiple signaling pathways modulate the expression and activity of Pgp in response to xenobiotics and disease. A non-genetic way of intercellular transfer of Pgp occurs in cancer cells, but whether this also occurs in non-cancer cells such as endothelial cells that form the BBB is not known. A human brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…As P-gp plays a role in preventing the entry of drugs into the brain, the effects of HDAC inhibitors VPA and TSA were tested on a human brain endothelial cell line (hCMEC/D3). Although the expression of VPA and TSA did not induce P-gp expression, it caused mobilization of P-gp between endothelial cells [117]. This non-genetic transfer of P-gp is a novel mechanism by which the functionality of the blood brain barrier is altered [117].…”
Section: P-glycoproteinmentioning
confidence: 87%
See 2 more Smart Citations
“…As P-gp plays a role in preventing the entry of drugs into the brain, the effects of HDAC inhibitors VPA and TSA were tested on a human brain endothelial cell line (hCMEC/D3). Although the expression of VPA and TSA did not induce P-gp expression, it caused mobilization of P-gp between endothelial cells [117]. This non-genetic transfer of P-gp is a novel mechanism by which the functionality of the blood brain barrier is altered [117].…”
Section: P-glycoproteinmentioning
confidence: 87%
“…Although the expression of VPA and TSA did not induce P-gp expression, it caused mobilization of P-gp between endothelial cells [117]. This non-genetic transfer of P-gp is a novel mechanism by which the functionality of the blood brain barrier is altered [117]. The transfer of P-gp has not been studied in tumor cells, and it will be interesting to see if similar mechanisms are induced in this context.…”
Section: P-glycoproteinmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, in different lung cancer cell lines, 3mM sodium butyrate significantly increased both mRNA and protein levels of MDR1 (Zhao et al, 2018). Similar to TSA and SAHA, VPA (0.3mM to 5mM) was able to modulate MDR1 expression and/or function in hCMEC/D3 brain endothelial cells (Noack et al, 2016;You et al, 2019b). However, 0.25mM sodium butyrate, which was the highest nontoxic concentration in hCMEC/D3 cells, did not significantly alter the mRNA or protein expression of MDR1 in those cells.…”
Section: Short Chain Fatty Acidsmentioning
confidence: 78%
“…Interestingly, conflicting results were observed with hCMEC/D3 brain endothelial cells. Noack and the colleagues showed that 0.33M TSA moderately altered MDR1 function, but not the protein expression, through increasing the cell-to-cell transfer of MDR1 protein (Noack et al, 2016). MDR1 intercellular transfer has been implicated in the acquisition of multidrug resistance in tumor cells (Levchenko et al, 2005).…”
Section: Hydroxamic Acidsmentioning
confidence: 99%